NEW EMBO MEMBER’S REVIEW: The integrin–actin connection, an eternal love affair - Brakebusch, Cord (Oxford University Press, 2003)
Integrin receptors connect the extracellular matrix to the actin cytoskeleton. This interaction can be viewed as a cyclical liaison, which develops again and again at new adhesion sites only to cease at sites of de-adhesion. Recent work has demonstrated that multidomain proteins play crucial roles in the integrin–actin connection by providing a high degree of regulation adjusted to the needs of the cell. In this review we present several examples of this paradigm and with special emphasis on the ILK–PINCH–parvin complex, which amply demonstrates how structural and signalling functions are linked together.